The Efficacy of Chemotherapy in Advanced-Stage Cervical Cancer on Vitamin A Serum: Efektivitas Kemoterapi pada Karsinoma Serviks Stadium Lanjut terhadap Serum Vitamin A - Raissa N. Rizal; Rizal Sanif; Amirah Novaliani; Theodorus (Indonesian Journal of Obstetrics and Gynecology, 2022)
Abstract Objective: To determine the efficacy of neoadjuvant chemotherapy on changes of vitamin A serum in advanced cervical carcinoma patient. Method: A randomized clinical trial was performed in the Oncology Gynecology Polyclinic and Ward of Dr. Mohammad Hoesin General Hospital, Palembang from September 2019 to September 2020. There were 30 subjects of advanced cervical carcinoma. Vitamin A levels and tumor volume subjects were assessed before and 1 month after 3 cycles of NAC and analyzed using the Paired T Test and Wilcoxon test. The correlation between vitamin A levels and tumor volume was analyzed by using Spearman's Rho test. Data analysis was using SPSS version 22.0. Results: This study showed statistically not significant increase on vitamin A levels after 3 cycles of NAC chemotherapy (p=0.515). However, there was a significantly decrease in tumor volume after 3 cycles of NAC (p=0.000). In addition, there was a moderate negative correlation between tumor size and vitamin A (r=-0.475; p=0.008). Conclusion: It can be concluded that there was significantly decrease in tumor volume after 3 series NAC chemotherapy and the smaller tumor size, the higher level of vitamin A serum. Keywords: cervical cancer, neoadjuvant chemotherapy, randomized clinical trial, vitamin A, Abstrak Tujuan: Untuk mengetahui efektivitas kemoterapi neoadjuvan terhadap perubahan kadar serum vitamin A pada karsinoma servik stadium lanjut. Metode: Penelitian uji klinik tanpa pembanding telah dilakukan di Poliklinik dan Bangsal Onkologi Ginekologi RSUP Dr. Muhammad Hoesin Palembang sejak September 2019 hingga September 2020. Didapatkan 30 sampel karsinoma serviks stadium lanjut. Kadar vitamin A dan volume tumor dinilai sebelum dan 1 bulan setelah 3 siklus NAC dan dianalsis menggunakan uji Paired T Test dan Wilcoxon. Korelasi antara Kadar vitamin A dan volume tumor sampel dianalisis menggunakan uji Spearman Rho’s. Analisa data menggunakan SPSS versi 22.0. Hasil : Pada penelitian ini terdapat peningkatan tidak signifikan kadar vitamin A setelah kemoterapi (p = 0,515). Terdapat penurunan secara signifikan volume tumor sebelum dan sesudah kemoterapi NAC 3 seri (p = 0,000). Selain itu, didapatkan korelasi negatif sedang yang bermakna antara ukuran tumor dan kadar vitamin A ( r = -0,475 ; p = 0,008). Simpulan : Disimpulkan bahwa terdapat penurunan volume tumor setelah kemoterapi NAC 3 series dan semakin kecil ukuran tumor maka semakin tinggi kadar vitamin A dalam serum. Kata kunci: kanker serviks, kemoterapi neoadjuvan, uji klinik tanpa pembanding, vitamin A.